Analisis Risiko Investasi pada Portofoliodengan Value at Risk (VaR) Menggunakan Simulasi Monte Carlo - Afra Moudi Luthfiyanti; Media Rosha (Journal of Mathematics UNP, 2020)
Abstract— Investment is the placement of a number of funds at this time for the purpose to obtain a number of benefits in the future. In investing, Value at Risk is needed as a measurement tool that serves as a risk estimator that will occur. The method used to calculate VaR is the Monte Carlo Simulation method that performs simulations by generating random numbers. The data used in this study is secondary data, that is data on the closing price of Unilever and Telekomunikasi stock in the June 2019-November 2019 period. The data analysis technique used is calculate stock returns, conduct a normality test, simulate the return value using parameter estimation, estimate the maximum loss, calculate the VaR value and the average of VaR. Based on research result at a 95% confidence level, a period of one day and an initial investment fund is assumed  it is possibility of losses amounted to .Keywords— investment, Value at Risk (VaR), Monte Carlo simulation.